2016
DOI: 10.1002/pd.4948
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide copy number analysis on DNA from fetal cells isolated from the blood of pregnant women

Abstract: Intact fetal cells can be isolated from every maternal blood sample. Amplified DNA from isolated fetal cells enabled genetic analysis by array comparative genomic hybridization and next-generation sequencing. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 31 publications
(48 reference statements)
8
100
0
1
Order By: Relevance
“…In another pregnancy carrying a fetus which was mosaic for monosomy X and a cell line with telomeric deletions on chromosome X, we could detect a complete loss of chromosome X and subtelomeric deletion in the DNA from two individual fetal cells respectively [26]. The results were confirmed by CMA and NGS on an amniocentesis sample.…”
Section: Dna Fidelitysupporting
confidence: 55%
See 3 more Smart Citations
“…In another pregnancy carrying a fetus which was mosaic for monosomy X and a cell line with telomeric deletions on chromosome X, we could detect a complete loss of chromosome X and subtelomeric deletion in the DNA from two individual fetal cells respectively [26]. The results were confirmed by CMA and NGS on an amniocentesis sample.…”
Section: Dna Fidelitysupporting
confidence: 55%
“…This method of targeting EVTs has been very reliable in enriching fetal cells from every pregnant sample. Fetal cells enriched this way have subsequently been used to detect chromosomal and subchromosomal changes in the fetal genome, thus confirming EVTs to be relevant targets in cbNIPD [17].…”
Section: Trophoblastsmentioning
confidence: 75%
See 2 more Smart Citations
“…In conventional cffNIPT, the DNA is fragmented and contami­nated with maternal DNA making it difficult to detect small copy number variations in the fetal genome. Since fetal cells encompass the uncontaminated fetal genome, cbNIPT paves the way for progress in noninvasive prenatal testing [8]. Vestergaard et al [9] previously demonstrated that aneuploidies and even sub-chromosomal aberrations can be detected using this cbNIPT technology.…”
Section: Introductionmentioning
confidence: 99%